Predictive effects of advanced lung cancer inflammation index and serum vitamin D on mortality in patients with asthma - Ting Li; Qi Wang; Yuhan Li; Wenyong Zhang; Manyu Chen; Bihua Deng; Lin Liang; Weixian Lin; Yuying Lin; Ying Meng (Nutrition Journal)
Abstract Background Changes in systemic inflammation, nutritional status and serum vitamin D level are important characteristics of asthma. However, role and importance of nutritional inflammatory indicators or serum vitamin D concentrations in predicting the prognosis of asthma remain unclear. The advanced lung cancer inflammation index (ALI), based on body mass index (BMI), serum albumin and neutrophil–lymphocyte ratio (NLR), is a comprehensive index to assess systemic inflammation and nutrition. This study aimed to evaluate their independent and combined predictive value of mortality in asthma patients. Methods This study analyzed data from the National Health and Nutrition Examination Survey (NHANES) 2001–2018. Cox regression analysis was used to assess the independent or joint effect of ALI and serum vitamin D on mortality risks of asthma. Receiver operator characteristic curve analysis was used to compare the prognostic ability of ALI with its component factors, including NLR, albumin, neutrophil, lymphocyte and BMI. Results A total of 2870 eligible asthma patients were included. After adjustment, higher ALI correlated significantly with reduced all-cause and respiratory disease mortality (adjusted hazard ratio [aHR] = 0.64 and 0.34; P < 0.05). Meanwhile, vitamin D deficiency correlated significantly with increased all-cause and respiratory disease mortality (aHR = 2.06 and 2.73; P < 0.05). The area under the curve of ALI in predicting 1-year, 5-year or 10-year all-cause mortality surpassed that of its five component indices. Joint analyses showed that individuals with higher levels of ALI and vitamin D had the lowest risks of all-cause and respiratory disease mortality (aHR = 0.31 and 0.17; P < 0.05). Conclusions ALI and serum vitamin D are robust independent and combined predictors of mortality in asthma patients. ALI offers superior predictive capability over its components, and sufficient vitamin D levels are beneficial for survival outcomes. The synergistic effect of high ALI and adequate vitamin D highlights the benefit of integrating both metrics into clinical practice for enhanced prognostic accuracy.